Synthesis and Application of Poly(N-isopropylacrylamide-co-methacrylic Acid) Hydrogels as Sorbent Materials for Wastewater Treatment - Aleksandar Zdravković; Vesna Nikolić; Snežana Ilić-Stojanović; Sanja Stojanović; Ana Dinić; Maja Urošević; Ivana Gajić; Ljubiša Nikolić (Separations)
N-isopropylacrylamide and methacrylic acid were copolymerized by a free radical polymerized mechanism. The obtained hydrogel poly(N-isopropylacrylamide-co-methacrylic acid) hydrogels, poly(NIPAM-co-MAA), were utilized as sorbent material for removal Cr(VI), Mn(II), and Pb(II) ions from simulated aqueous solutions. Hydrogel structures before and after heavy metal sorption are characterized by Fourier transform infrared spectroscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The swelling results indicate that poly(NIPAM-co-MAA) hydrogels are pH- and temperature-sensitive and have high swelling reversibility through three swelling/contraction cycles. The studied parameters of heavy metal sorption include the effect of pH, the initial concentration of heavy metal, the effect of temperature, and the desorption of metal ions. The maximum sorption capacities of poly(NIPAM-co-MAA) hydrogels were determined at pH 4.5 and 25 °C, and they are, for Cr(VI), Mn(II), and Pb(II) ions, 289.35 mg/g, 190.59 mg/g, and 349.71 mg/g, respectively. The pseudo-second-order model and the Langmuir adsorption isotherm best describe the sorption of heavy metal ions onto hydrogels. The removal of heavy metals is an exothermic reaction, and the interaction mechanism between the metal and the hydrogel is primarily physical in nature. Results of three sorption/desorption cycles show a good desorption ratio and sorption capacity of poly(NIPAM-co-MAA) hydrogels.